2018
DOI: 10.1103/physreve.97.012403
|View full text |Cite
|
Sign up to set email alerts
|

Role of spatial heterogeneity in the collective dynamics of cilia beating in a minimal one-dimensional model

Abstract: §Cilia are elastic hairlike protuberances of the cell membrane found in various unicellular organisms and in several tissues of most living organisms. In some tissues such as the airway tissues of the lung, the coordinated beating of cilia induce a fluid flow of crucial importance as it allows the continuous cleaning of our bronchia, known as mucociliary clearance. While most of the models addressing the question of collective dynamics and metachronal wave consider homogeneous carpets of cilia, experimental ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…As very recently pointed out in [47], theoretical studies investigating the collective dynamics of hydrodynamically interacting cilia have, so far, usually considered homogeneous carpets of cilia. In [47] the role of a spatial heterogeneous ciliary distribution on coherent ciliary beating using one dimensional arrays of cilia represented by rowers has been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As very recently pointed out in [47], theoretical studies investigating the collective dynamics of hydrodynamically interacting cilia have, so far, usually considered homogeneous carpets of cilia. In [47] the role of a spatial heterogeneous ciliary distribution on coherent ciliary beating using one dimensional arrays of cilia represented by rowers has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…As very recently pointed out in [47], theoretical studies investigating the collective dynamics of hydrodynamically interacting cilia have, so far, usually considered homogeneous carpets of cilia. In [47] the role of a spatial heterogeneous ciliary distribution on coherent ciliary beating using one dimensional arrays of cilia represented by rowers has been investigated. It is particularly shown that the phase coherence of random clustered distributions of rowers are less sensitive to variations of the number density than (homogeneously) random distributions of rowers.…”
Section: Discussionmentioning
confidence: 99%
“…, N. The phase variable φ i represents the beating motion of the i-th cilium characterized with its own natural driving frequency ω i . With an assumption of cilium-to-cilium heterogeneity, which is supported by experimental observations [17,18], the natural frequency ω i in the first term could be chosen from a distribution function, g(ω). In this study, we consider a Gaussian function, g(ω i ) = N(ω m , σ 2 ), with the mean ω m and variance σ 2 , as a model of heterogeneous cilia population.…”
Section: Introductionmentioning
confidence: 99%
“…Sustained oscillations are ubiquitous in biological systems from oscillating gene products inside cells to spontaneous beating of cilia and flagella on the cell surface microorganisms and airway epithelium [1]- [3]. Diverse cell types are known to encode genetic oscillators or clocks that function in circadian timekeeping [4], [5], cell cycle regulation [6], [7] and rhythmic structure formations across organisms during development [8]- [10].…”
Section: Introductionmentioning
confidence: 99%